The Websites of Private Universities between Hybrid Education And Promotion in the Light of Crises: An Applied Study - Shoaib, Haneen (The Arab Journal of Administration, 2022)
The study aims to determine the role of the private Universities websites in improving performance in light of crises, and spreading awareness of the importance of the role of websites in improving performance. It also clarifies the role of websites in improving performance through the application of blended learning, and improving promotional activities from the students’ point of view. The study found a statistically significant effect of Universities’ use of websites in improving performance by providing hybrid education and electronic promotion. It also found that there is a vast inexperience of most personnel in the Universities under study in relation to the use of accurate techniques for managing websites on the Internet. Also, the websites utilization is not ideal in promotion management in private Universities from the students’ point of view. The study recommends the necessity of increasing opportunities for mutual interaction between students and teachers by developing learning models using hybrid education. Moreover, to increase the efficiency of the personnel in charge of educational technology through training, as well as to have a complete transformation into distance education. Finally, it suggests that this take place through supporting University’s websites with all available means to develop promotional techniques.